Geocultural diplomacy. Issue 4 (7th June 2022) - Winter, Tim
ABSTRACT: New modes of analysis are required to account for current developments in international cultural politics. To that end, this paper introduces the concept of geocultural diplomacy. It seeks to move beyond current debates about cultural diplomacy, which foreground the nation-state and suffer from narrowly conceived definitions of culture. The concept of the geocultural is offered to explore new developments in world affairs that demand more critical attention.The paper focuses on the example of the Silk Road, which, through its Belt and Road Initiative, China now proclaims to be 'reviving' for the twenty-first century. Three themes – narrative, materiality, values – critically consider how geocultural forms can emerge and stabilize as contexts across which complex, multi-actor diplomatic and cooperative structures form. Through this lens, we begin to see China's desire to build regional alliances combines internationalist values of peace, harmony and openness with strategic national interests.